2016
DOI: 10.1159/000445552
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the High Density Lipoprotein and its Subtypes in Coronary Heart Disease

Abstract: Background/Aims: To detect the changes of high density lipoprotein (HDL) and its subtypes in serum of patients with coronary heart disease (CHD). Methods: 337 hospitalized patients were selected from our hospital during August, 2014 - January, 2015, and divided into CHD group (n = 190) and control group (n = 127). Lipoprint lipoprotein analyzer was used to classify low density lipoprotein (LDL) particle size and its sub-components, as well as HDL particle size and its sub-components. The changes of the subtype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…In accordance with our results, De la Llera-Moya et al [32] reported that LPS-induced endotoxemia in healthy volunteers led to a depletion of pre-beta1a and small- and medium-sized HDL particles, determined by 2D eletrophoresis and nuclear magnetic resonance. Interestingly, small HDL particles were shown to be more antioxidant and more anti-inflammatory in cardiovascular disease [33], but large HDL particles as determined by Lipoprint technology appear to be more associated with a reduced risk of coronary artery disease [17, 18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with our results, De la Llera-Moya et al [32] reported that LPS-induced endotoxemia in healthy volunteers led to a depletion of pre-beta1a and small- and medium-sized HDL particles, determined by 2D eletrophoresis and nuclear magnetic resonance. Interestingly, small HDL particles were shown to be more antioxidant and more anti-inflammatory in cardiovascular disease [33], but large HDL particles as determined by Lipoprint technology appear to be more associated with a reduced risk of coronary artery disease [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…In the cardiovascular field, both HDL cholesterol (HDL-C) concentration and HDL particle size were independently associated with cardiovascular risk [16]. In particular, large HDL particles appear to be protective in coronary artery disease [17, 18]. To our knowledge, HDL size has never been explored in septic patients.…”
Section: Introductionmentioning
confidence: 99%
“…It is now accepted that the importance of HDL in the progression of CVD, resides on their quality rather than their quantity, highlighting the importance of their composition, structure, and function [10,11,12,13]. Indeed, apolipoprotein A–I (Apo A–I), the major protein component of HDL, has cardiovascular protective properties [14,15]. Also, low levels of apolipoprotein E (Apo E) have been related to hyperlipidemia and atherosclerosis [16].…”
Section: Introductionmentioning
confidence: 99%
“…SAA has been shown to displace some of the primary protein component of HDL, apolipoprotein A‐I (ApoA‐I), during acute inflammation, resulting in altered HDL functionality (O'Brien & Chait, 2006 ; Bindu et al, 2011 ). The presence of SAA has been shown to reduce the normal anti‐inflammatory activity of HDL (Jahangiri et al, 2013 ; Gao et al, 2016 ). This leads to the activation of proinflammatory and proatherogenic pathways through increased interactions with toll‐like receptors 2, and 4 (TLR‐2 and TLR‐4) to promote the release of proinflammatory cytokines, FPRL‐1 to promote chemotaxis towards the site of infection/injury, and CD36 to promote lipid uptake (Buck et al, 2016 ; Bindu et al, 2011 ; Eklund et al, 2012 ; Migita et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%